Neutrophil extracellular trap biomarkers in aneurysmal subarachnoid hemorrhage: early decline of DNase 1 activity associated with delayed cerebral ischemia - Hendrix, Philipp; Witsch, Jens; Spalart, Valérie; Schneider, Hauke; Oertel, Joachim; Geisel, Jürgen; Martinod, Kimberly; Hemmer, Sina (Frontiers in Neurology, 2024)
Introduction High mobility group box 1 (HMGB1) protein is a critical mediator of neutrophil extracellular trap (NET) formation (NETosis). Myeloperoxidase (MPO)-DNA complexes, a biomarker of NETs, and HMGB1 have been associated with delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage (aSAH). Additional mechanistic NET-related biomarkers and their role in the neuroinflammatory cascade surrounding DCI remain to be explored. Methods A posthoc analysis of a prospective, blinded, single-center biomarker observational study was performed. De novo measurements of serum citrullinated histone H3-DNA complexes (H3Cit-DNA), peptidylarginine deiminase 4 (PAD4), cell-free DNA (cf-DNA) and DNase 1 activity were conducted on admission (D0) and day 4 (D4). Delayed cerebral infarction (DCI) was defined as new cerebral infarction on CT-head not present on post-treatment scan. Results H3Cit-DNA, PAD4, cf-DNA, and DNase 1 activity were within quantifiable ranges in all serum samples analyzed at D0 and D4. Admission biomarker levels were not associated with DCI development. From D0 to D4, in both the DCI and the non-DCI groups, H3Cit-DNA levels significantly decreased, cf-DNA levels significantly increased, and PAD4 levels remained stable. In contrast, DNase 1 activity significantly decreased from D0 to D4 in the DCI group (p<0.001) but not in the non-DCI group. Conclusion This exploratory analysis demonstrated NET-related biomarkers H3Cit-DNA, PAD4, cf-DNA and DNase 1 activity in all aSAH patients. A decline of systemic DNase 1 activity in the early phase might increase the risk of delayed cerebral ischemia.